Diabetes Patients Compliance Towards Routine Care Schedule at Health Care Centers During Covid-19 Pandemic - Rezha Andico Eka Pratama; Susana Widyaningsih (Proceedings Series on Health & Medical Sciences, 2022)
Background: One of the major health problems of the twenty-first century is chronic disease, which sometimes has the potential to get worse. Chronic diseases of concern include cardiovascular, cancer, chronic respiratory, and diabetes mellitus. The total of Diabetes Mellitus in Hospital in 2022 is 140 patients. During the Covid-19 pandemic, many people with diabetes mellitus did not undergo routine treatment at the hospital, they said they were afraid to go to the hospital because they received information that the hospital was more susceptible to Covid-19, so patients were reluctant to go for routine treatment. Objective: The objective of this study is to describe the compliance of diabetes mellitus patients to undergo routine care at the Health Service Center during the Covid-19 pandemic. Method: This study uses quantitative research methods. The design used in this study is a cross sectional approach. The location of the research was in Ajibarang Hospital and Ajibarang Health Center. Results: This study concluded that the level of patient compliance in routine care during the Covid- 19 pandemic was in the moderate category. With an average value of the total "Yes" answer of 71%, and it falls in the 51%-80% interval. Conclusion: There is a description of the compliance of diabetes mellitus patients with routine care during the covid-19 pandemic in the high category, which is 95%.